PERAN LURAH DALAM MENDORONG PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PAJAK BUMI DAN BANGUNAN - Hasratul Qadar; Subhilhar Subhilhar; Agus Suriadi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
This study aims to examine the role of the Village Head of Pulo Brayan Bengkel, East Medan District, in increasing the participation of the community in the implementation of the UN. The method used in this research is concurrent mix method. The data collection techniques used in this study are questionnaires, in-depth interviews, observation, literature study, and documentation. Data analysis technique used in this research is concurrent triangulation that is quantitative and qualitative data is done simultaneously in one stage of research. The results showed that there are still people in Pulo Brayan Bengkel Village who have not fulfilled their duties as tax payers. This is evidenced by the realization of UN revenue that is still far from the target.